Antibacterial Activity of Lactic Acid Producing Leuconostoc mesenteroides QZ1178 Against Pathogenic Gallibacterium anatis - Zhang, Hua; HuangFu, HePing; Wang, Xing; Zhao, ShanShan; Liu, Yuan; Lv, Haoxin; Qin, GuangYong; Tan, Zhongfang (Frontiers in Veterinary Science, 2021)
Lactic acid bacteria (LAB) convert carbohydrates into organic acids [mainly lactic acid (LA)], which reportedly have bactericidal activities. Gallibacterium anatis is a Gram-negative bacteria which infects birds, and causes significant economic losses. In this study, we investigated the antibacterial activity of the LA producing, Leuconostoc mesenteroides QZ1178 from Qula (fermented food), against G. anatis, using the Oxford cup method. Our data showed that L. mesenteroides QZ1178 inhibited G. anatis isolates from different origins; however, L. mesenteroides QZ1178 antibacterial activity dropped dramatically at pH 5.5–pH 6. The LA concentration and pH of the liquid broth containing L. mesenteroides QZ1178 after 24 h culture was 29 mg/mL and 3.6, respectively. This concentration (29 mg/mL at pH 3.6) and the antibiotic, cefotaxime (minimum inhibitory concentration (MIC) 2.5 μg/mL) effectively inhibited G. anatis (GAC026) growth as observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Gallibacterium anatis treated with LA exhibited extensive cell surface collapse, increased cell damage, cell membrane disruption, and cytoplasmic leakage, indicative of cell lysis. We suggest L. mesenteroides QZ1178 exerts potential antibacterial effects against the poultry pathogen, G. anatis via LA.